Environmental and Epidemic Sensitivity in the Context of Preserving Personal Health during Wartime - Kredentser, Oksana; Tytarenko, Tetiana; Dvornyk, Maryna; Larina, Tetiana; Savinov, Volodymyr; Savchenko, Aglaya; Paskevska, Iuliia (Social Welfare: Interdisciplinary Approach, 2026)
This article examines environmental and epidemic sensitivity as a psychological factor influencing health preservation during wartime. Based on a quantitative study involving 6042 adult respondents of varying ages, genders, educational and professional backgrounds, the research identifies key socio-demographic and social predictors of heightened sensitivity to ecological and health-related threats. The results show that women, individuals with higher education, older adults, and professionals in socially oriented fields (e.g., healthcare, education, safety services) report significantly higher levels of sensitivity. Furthermore, the quality and accessibility of medical services, health-supportive infrastructure, and the surrounding social environment were found to be significant contributors to environmental and epidemic sensitivity. These findings suggest that sensitivity in this context reflects not only emotional responsiveness but also a conscious cognitive and behavioural orientation toward health protection and environmental awareness. The study supports the view that, in the context of war-related stressors, environmental and epidemic sensitivity becomes an adaptive mechanism that can serve as a predictor of health-oriented behaviour and psychological resilience. The findings provide a basis for developing targeted psychoeducational and health-promotion interventions in crisis conditions.
Keywords: environmental and epidemic sensitivity; health preservation; wartime psychology; social predictors; stress adaptation